Synchronous-scan fluorescence and the complexation of copper (II) ions by humic substances - Lombardi,Ana T (1997)
Two fluorescence bands were detected using synchronous-scan fluorescence on samples of terrestrially derived humic substances (lex/lem 380/398, 440/458 nm) without the addition of copper. A third band (lex/lem 502/520 nm) was detected after severe quenching of the second band (lex/lem 440/458 nm) caused by additions of copper. A more energetic band (lex/lem 333/351 nm) is present in marine DOM, but absent in the terrestrial material. The effects of copper on both the intensity and shape of the synchronous-scan fluorescence spectra and this techniques potential use as a tracer are discussed.